Higit sa lahat - Fernandez, Gregorio; Lopez, Mario Mijares; De Leon, Narcisa B.; De la Rosa, Rogelio; Allegre, Emma; Silayan, Vic (LVN Pictures, 2004)
Roberto, a painter, pretended to be dead in a factory fire in order for his family to receive money as indemnity. Her wife suspected that he is still alive while he kept into hiding. One tradegy lead to another before the family was reunited.